MENYUSUN KARYA ILMIAH DI PERGURUAN TINGGI - Lubis, Nazriani; Lubis, Asnarni (Majalah Ilmiah METHODA, 2023)
Gatrell, et.al, and School Graduate wrote books containing how to write for a thesis, and dissertation. A book titled A Research Design and Proposal Writing in Spatial Science, Second Edition by Gatrell, et.all has a simple and complete explanation so that it is easy to understand and apply to final writing. Also, the book is supplemented with examples of several interesting titles to be the reference of the research authors, by explaining direct examples in explain background writing, survey libraries, research methods, how to explain the data used quantitative or qualitative to how to manage data correctly. The book How to Prepare Thesis Proposal A Guide for MPhil and PhD Students by School Graduates only explains the general lines of the chapters contained in a thesis. It was concluded that the book written by Gatrell, et.al was more dynamic in accordance with the needs of today’s academics since it also provides the components of crafting research grant fund proposal.